DEVELOPMENT WAY SOF MODERN PISTONS MUD PUMP (Oil and Gas Engineering, 2017)
Reviewed by growth of operating loads on the mud pump pistons. The possibilities of the use of polyure-thanes and the need to perform additional studies. The necessity of creating experimental unit for research of friction and wear mud pump pistons. A requirement to be met by the unit for research. Keywords: mud pump, piston, wear, friction, operation load.